ANALISIS PERBANDINGAN REGULASI PERLINDUNGAN HUKUM BAGI INVESTOR TERHADAP FORCED DELISTING MENURUT KEPUTUSAN DIREKSI PT BEJ NO. KEP-308/BEJ/07-2004 DENGAN POJK NO. 3/POJK.04/2021 - Dela Ulianda Simanjuntak (2022)
This study aims to determine the comparison of regulations made by the Indonesia Stock Exchange as a facilitator in securities trading with regulations made by the Financial Services Authority as a party that supervises the Capital Market sector in Indonesia. Legal protection for investors against forced delisting is reviewed from the comparison of the regulations of the Board of Directors of PT IDX and the OJK Regulations and related laws and makes the theory of legal responsibility and the theory of legal protection as a reference for this research. This study was included with a case study of a listed company that was affected by forced delisting before the promulgation of the OJK Regulation on the Implementation of Activities in the Capital Market Sector as well as an interview with the Indonesia Stock Exchange as a facilitator in securities trading in the Capital Market. The method used in this study is normative. The result of this study is that legal protection for investors against forced delisting is very much needed because this will cause losses for investors and the applicable regulations are the basis for implementing the protections that should have been given from the beginning in order to increase the sense of security in investing in the Capital Market. Many companies that have been cancelled from securities listing by the Stock Exchange cause losses to investors and there is no clear regulation regulating compensation arising from forced delisting actions before the issuance of OJK Regulation No. 3 / POJK.04 /2021 concerning the Implementation of Activities in the Capital Market Sector, this is a rare right thing that the OJK as a supervisorn in the Capital Market does in a role to protect investors against forced delisting.